Fungarium (2021)
Fungarium is a project that was born from the perceptions that people have about fungi, which are usually negative or unpleasant due to their little knowledge of this world. However, fungi are microorganisms that give us food, dyes, materials, among many other uses, that we as designers can take advantage to create new products or experiences. But how can we show the beauty of something that causes us disgust because of its appearance, color or form? This project seeks to give a new perspective to this world through an ornamental piece made with filamentous fungi, exalting its colors, shapes and textures, in order to achieve a catalysis that encourages research and the use of fungi in the field of biodesign.